Postural Stability in Children with High Sacral Level Spina Bifida: Deviations from a Control Group - DAĞÇINAR, ADNAN; GÖKCE, İBRAHİM; KARADAĞ SAYGI, NAİME EVRİM (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Objective: To assess static and dynamic postural stability changes in children with high sacral level spina bifida. Methods: Thirty-five children with high sacral level spina bifida and 35 age-matched healthy controls were enrolled. Their lower extremity muscle strengths and static and dynamic postural stability parameters were measured with the use of a dynamometer and the NeuroCom Balance Master(?) device, respectively. Functional gait and balance were evaluated using the five times sit-to-stand test (5STS) and the 6-minute walk test (6MWT). Spinal, hip, and ankle deformities of the patient group were measured by radiologic evaluation. Results: In comparison with controls, patients were found to have lower ankle dorsiflexion and plantar-flexion strength, increased 5STS duration, and decreased 6MWT distance while both static and dynamic postural stability parameters were significantly different. Bilateral ankle muscle strengths were found to be negatively correlated with postural stability parameters. The presence of hydrocephalus or meningomyelocele in the patient group was found to have negative effects on static postural stability. Conclusion: Static and dynamic postural stability is affected even in children with high sacral level spina bifida who are expected to have best condition in this patient population. The ankle muscle strength is the main factor influencing these changes.
Keywords: motor control; muscle strength; postural stability; spina bifida; GAIT; MYELOMENINGOCELE; RELIABILITY; STRENGTH; BALANCE; VALUES